The reform of the Cuban economy. Evaluation of its potencial impact on the economic growth - Palacios Cívico, Juan Carlos (Papeles de Europa, 2012)
This paper analyzes the deep transformations purposed in the VI Cuban Communist Party Congress, the way they will contribute to the economic growth, the solution of the main restrictions of the Cuban economy, and those outstanding points which have not been included in the political agenda. The analysis starts from the hypothesis that Cuban economic growth is restricted by the lack of foreign currency and a very centralized regulatory framework, based on the theoretical and empirical surveys about economic growth, bibliographic analysis about the Cuban economy over the last decades and the fieldwork carried out by author from September 2010 to May 2011.
Keywords: economic reforms; Cuban socialism; efficiency; economic growth